Modelling and simulating retail management practices: a first approach. (22nd January 2010) - Siebers, Peer-Olaf; Aickelin, Uwe; Celia, Helen; Clegg, Chris W.
Management practices play a vital role in determining the success or failure of retail organisations. There has been a significant amount of modelling and simulation of operational management practices. However, people management practices including training, empowerment, and teamwork have often been neglected despite evidence to suggest that they crucially impact upon an organization's performance. In this paper we focus on simulating various in-store scenarios grounded in empirical case studies with a leading UK retailer. Ultimately, we want to determine if agent-based modelling and simulation can assist in the assessment of the impact of people management practices on customer satisfaction and sales.